Optimized hydrophobic magnetic nanoparticles stabilized pickering emulsion for enhanced oil recovery in complex porous media of reservoir - Hu, Xiaojuan; Long, Yunqian; Xuan, Gong; Wang, Yuyi; Huang, Xiaohe; Xu, Yupeng; Liu, Jing; Wang, Bohong; Song, Fuquan (Frontiers in Energy Research, 2023)
With an extensive application of flooding technologies in oil recovery, traditional emulsion flooding has seen many limits due to its poor stability and easy demulsification. Pursuing a new robust emulsion plays a fundamental role in developing highly effective emulsion flooding technology. In this work, a novel Pickering emulsion with special magnetic nanoparticles Fe3O4@PDA@Si was designed and prepared. To disclose the flooding mechanism from magnetic nanoparticles, the physico-chemical characterization of Fe3O4@PDA@Si was systematically examined. Meanwhile, the flooding property of the constructed Pickering emulsion was evaluated on the basis of certain downhole conditions. The results showed that the synthesis of Fe3O4@PDA@Si nanoparticles was found to have a hydrophobic core-shell structure with a diameter of 30 nm. Pickering emulsions based on Fe3O4@PDA@Si nanoparticles at an oil-to-water ratio of 5:5, 50°C, the water separation rate was only 6% and the droplet diameter of the emulsion was approximately 15 μm in the ultra-depth-of-field microscope image. This demonstrates the excellent stability of Pickering emulsions and improves the problem of easy demulsification. The microscopic flooding experiment demonstrated that profile control of the Pickering emulsion played a more important role in enhanced recovery than emulsification denudation, with the emulsion system increasing oil recovery by 10.18% in the micro model. Core flooding experiments have established that the incremental oil recovery of the Pickering emulsion increases with decreasing core permeability, from 12.36% to 17.39% as permeability drops from 834.86 to 219.34×10-3 μm2. This new Pickering emulsion flooding system stabilized by Fe3O4@PDA@Si nanoparticles offers an option for enhanced oil recovery (EOR).